Environmental public policies and sustainable tourism development in Ecuador’s protected areas - Mendoza-Montesdeoca, Iván; Rivera-Mateos, Manuel; Doumet-Chilán, Neme Yamil (Revista de Estudios Andaluces, 2022)
Critical analysis of public policies on environmental conservation, management, and tourism development in the protected natural areas of Ecuador to detect their dysfunctions, contradictions, and problems of applicability. A predominantly exploratory research methodology with a descriptive-analytical approach is used when studying and systematizing the different regulations, actions and guidelines existing and implemented by international and national organizations with competencies in environmental conservation and sustainable development. These are systematized and analyzed through the main documents of interest that include principles, strategic guidelines, and specific rules of application.Through primary and secondary sources, and internal documentation of various Administrations we have identified the most visible effects and impacts that these policies have generated in the protection and/or valorization of the natural heritage, as well as in the tourist development compatible with the conservation of these spaces, the generation of complementary income and economic diversification for local communities. We concluded that Ecuadorian regulations on the conservation of protected areas present notable points of collision and lack of coherence or coordination with tourism policies. This is the consequence of two main factors: the lack of a broad strategic vision and comprehensive territorial planning of these territories as sustainable tourist destinations and the lack of a framework for management, planning and collaborative planning between the different local agencies and agents that affect these spaces.